Thyroid function status in patients with thyroid associated ophthalmopathy: a study for Nepal - Piya, Saurav; Gurung, Jeena; Khatri, Anadi (Journal of Diabetes and Endocrinology Association of Nepal, 2019)
Introduction: Thyroid Eye Disease (TED) is an organ-specific autoimmune inflammatory incapacitating eye disorder usually associated with Graves’ disease affecting the orbit. Objectives: To determine thyroid function status in patients with thyroid-associated Ophthalmopathy. Methods: This is a hospital-based cross-sectional study of sixty three clinically diagnosed new cases of thyroid-associated ophthalmopathy done at Nepal Eye Hospital, Kathmandu from February 2012 to January 2013. Detailed history, systemic & ocular examination with special emphasis on evaluation of extraocular movement, lid signs, exophthalmos with Hertel's exophthalmometer was done. Thyroid function test and endocrine consultation were also done in all cases. Results: There were an equal distribution of TED with hyperthyroid (34.95%) and euthyroid status (34.95%). The most common presentation of both euthyroid and hypothyroid patient was tremor (13.4%) and palpitation (13.45%). The most common symptom of TED was foreign body sensation (54 %) but in TED with euthyroid and hypothyroid status, redness (22.2 %) and diminution of vision (20.6 %) were more frequent symptoms respectively. The most common presenting sign was Von Graefe’s sign (69 %). Among TED with hyperthyroid and hypothyroid status, Dalrymple's sign (29.3%) and Mobius sign (17.4%) were most common respectively. Conclusion: Thyroid-associated ophthalmopathy is an important health concern among patients with a thyroid disorder. TED with hyperthyroid states present more severely than hypothyroid and euthyroid states. As TED occurred with a high prevalence in all thyroid states, a close collaboration between endocrinologists and ophthalmologists along with timely referrals of patients with any eye complaint is mandated.